ANALISIS PELAKSANAAN ASSESSMENT PEMBELAJARAN IPA DI SMPN 01 GRESIK SELAMA PEMBEAJARAN ONLINE MASA PANDEMI COVID-19 - Agus Hasyim Muzadi; Wahono Widodo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
This research was conducted with the aim of knowing the description of the implementation of the science learning assessment carried out by science teachers at Junior High School 01 Gresik during the pandemic Covid-19, to find out the obstacles of science teachers at Junior High School 01 Gresik in carrying out assessments science learning during the pandemic Covid-19, and to find out the right solutions and suggestions for improvement for the implementation assessment of the science learning at Junior High School 01 Gresik during the pandemic Covid-19. The research design used descriptive analysis method with quantitative and qualitative approaches. Subjects in this study were teachers in Natural Sciences subjects at Junior High School 01 Gresik. The instruments used in the study were questionnaires, documentation and interviews. The results in this study were a decrease in the percentage of implementation of the assessment of science learning at Junior High School 01 Gresik from 76.5% in the good category, decreasing to 60.2% with a fairly good category in online learning during the Covid-19 pandemic. Limitations and obstacles on the implementation of online learning during the pandemic have become one of the main factors in the decrease in the percentage of implementation assessment of the science learning at Junior High School 01 Gresik. These limitations and obstacles include the lack of awareness of students in doing assignments on time, limited tools and materials to carry out practicum from home, not all materials can be practiced at home, and limited aspects that can be assessed from the affective of students during online learning. Efforts and solutions that have been implemented by the teacher at Junior High School 01 Gresik include monitoring students, communicating with student guardians, home visits, and allowing problematic students to use existing devices at school during online learning.